THU0057 Mechanical strain determines the site-specific direction of inflammation and tissue damage in arthritis. (12th June 2018) - Cambré, I.; Gaublomme, D.; Burssens, A.; Jacques, P.; Meuris, L.; Lambrecht, S.; Carter, S.; De Muynck, A.; Callewaert, N.; Kollias, G.; Lories, R.; Schett, G.; et al.
Abstract : Background: Many pro-inflammatory pathways leading to arthritis act systemically on the immune system rather than locally in the joint. However, the reason behind the regional and patchy distribution of arthritis represents a longstanding paradox. Objectives: To explore the relation between mechanical strain and joint inflammation and to understand the underlying basis of joint pattern involvement in inflammatory rheumatic diseases. Methods: Arthritis was induced by collagen-induced arthritis (CIA) and passive collagen antibody induced arthritis (CAIA) in respectively C57BL/6 and RAG2-/- (T- and B-cell deficient) mice. Animals were subjected to different regimens of mechanical strain. Increased strain occurred in voluntary running mice whereas tail suspension (unloading) abolished mechanical strain; both were compared to control housing conditions. The impact of different loading conditions was measured on clinical disease score, histology, micro-CT images and erosion quantification, gene induction in tendon and synovial tissue, immune cell recruitment in situ, development of anti-collagen antibodies and their pattern of siaylation and galactosylation. Results: Voluntary running of CIA in C57BL/6 mice markedly induced an early onset and increased progression whereas no disease onset could be observed in the hind paws from animals in unloaded conditions. CAIA in running RAG2-/- mice also induced early arthritic symptoms and severe progression. Intriguingly, running conditions were sufficient to induce arthritis without the need of LPS as an inflammatory trigger. Mechanical strain did not alter however IgG autoantibody levels nor their levels of galactosylation and sialylation. Furthermore, we demonstrate that mechanical strain on stromal cells results in recruitment of classical monocytes into specialised mechano-sensitive regions characterised by a unique microanatomy. This promotes local inflammation and differentiation into local osteoclasts which induce regional erosions. A striking similarity was observed in the pattern of joint erosions in human patients with RA and SpA which were also confined to these mechanosensitive regions. Conclusions: This study provides the first evidence that mechanical strain controls the transition from systemic autoimmunity into site-specific joint inflammation. Homing of inflammation and development of erosions was confined to specific mechano-sensitive regions, characterised by a high number of attachment- and contact points for tendons. This represents a novel paradigm and explains why arthritis in mice and humans is characterised by a regional and patchy distribution. Curiously, this pathway does not rely on adaptive immunity but rather on stromal cells. Mechano-stimulation of mesenchymal cells induced CXCL1 and CCL2 permitting recruitment of classical monocytes which can differentiate into bone-resorbing osteoclasts. Thus, mechanical strain controls the site-specific direction of inflammation and tissue damage in arthritis. Acknowledgements: Disclosure of Interest: None declared